Clinico-Epidemiological Study of Canine Neoplasms - Patel, Disha U; Bhatt, Raghuvir H; Dodia, Vaibhavsinh D; Vadalia, Jignesh V; Padaliya, Nilesh R; Talekar, Shivaji H (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The present study was carried out to know the retrospective clinico-epidemiology of canine neoplasms based on total 9972 canine  clinical cases registered at Veterinary Clinical Complex of the College at Junagadh (India) during the three years (April, 2018 to May,  2021). Among them, 2685 (26.92%) cases were of different types of surgical affections, of which 121 (4.50%) animals were confirmed with  neoplasms. The clinical epidemiology of 121 registered cases of canine neoplasms revealed higher incidences of tumour in 4-8 years of  age group (51.23%), followed by 9 to 12 years (28.09%), while sex-wise occurrence was more in females (61.98%) compared to males.  Breed-wise data revealed Labrador retriever (25.61%) followed by German Shepherd (23.14%), Pomeranian (20.66%), and non-descript  (18.18%) breeds had higher occurrence of neoplasm than other breeds. Canine mammary gland tumours were most commonly found  (28.09%) followed by cutaneous tumour (23.14%), transmissible venereal tumour (21.048%) and others during the study.
Keywords: Canine Mammary gland tumour; Canine Neoplasm; Incidence; Tumour